4x+(x-3)6=92

Simple and best practice solution for 4x+(x-3)6=92 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+(x-3)6=92 equation:


Simplifying
4x + (x + -3) * 6 = 92

Reorder the terms:
4x + (-3 + x) * 6 = 92

Reorder the terms for easier multiplication:
4x + 6(-3 + x) = 92
4x + (-3 * 6 + x * 6) = 92
4x + (-18 + 6x) = 92

Reorder the terms:
-18 + 4x + 6x = 92

Combine like terms: 4x + 6x = 10x
-18 + 10x = 92

Solving
-18 + 10x = 92

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 10x = 92 + 18

Combine like terms: -18 + 18 = 0
0 + 10x = 92 + 18
10x = 92 + 18

Combine like terms: 92 + 18 = 110
10x = 110

Divide each side by '10'.
x = 11

Simplifying
x = 11

See similar equations:

| 3.25-y=0.75 | | F(x)=-x^2+3x-2 | | 12-(3m+3)=2+3m-11 | | 5A+2(3A-5)=1+5(A+2)-A+3(3-4) | | 6x+2x-4=3x-3+12 | | 4t+35=10t-37 | | 2b+4=-18+-9 | | 2y+x-3=0 | | 8m+4=8m | | (x-380)(x^2+2)=0 | | 2x+x+y=180 | | 4x+(4x-3)6=92 | | 2(x-5)=7x+6x | | x+30=4x+9 | | 10=60-5x | | 8-5X-10X+6= | | 3w=w-30 | | 2x-(-4)+3=2x-1 | | 3x-4(9-2y)+5x=2y+3(x-y) | | 2c-6=2(c-3) | | 3x+4(2x-7)+12=4+5(3x+4) | | a+39=5a-37 | | 3x^2-130x-1000=0 | | 5m+1m=100 | | 2x^3+5x-9=0 | | (x+1)(4-3i)(4+3i)=0 | | 17=-5(3+w)+w | | 3x+4(x-5)=1-5(x-3) | | 4m+1m=100 | | X^2+4x+4=289 | | 16q+17q=20 | | 10x-20x=30 |

Equations solver categories